EVALUASI PENGGUNAAN APLIKASI ZOOM MEETING DALAM PROGRAM TAHFIZH AL-QUR’AN DI SD KHOIRU UMMAH CIANJUR - Taofik Andi Rachman; Euis Latipah; Mohamad Erihadiana (Universitas Pakuan, 2021)
EVALUATION OF THE USE OF THE ZOOM MEETING APPLICATION IN THE TAHFIZH AL-QUR'AN PROGRAM AT KHOIRU UMMAH CIANJUR ELEMENTARY SCHOOLAt the time of the COVID-19 pandemic, every school in Cianjur, especially Khoiru Ummah Cianjur the Tahfizh School held a distance learning system. One of the applications used during distance learning is the Zoom Meeting Meeting application. This research was conducted to determine the effectiveness of using the Zoom Meeting Meeting on learning outcomes of Tahfizh Al-Qur'an. This research is qualitative in nature and uses the case study method. The data collection technique was done by observing, documenting and interviewing the tahfizh guidance teachers. The results of this study indicate that the use of the Zoom Meeting Meeting application is effective for students in this tahfizh school in achieving memorization targets and even exceeding them. The Zoom Meeting Meeting application is effective because communication between the teacher and participants is face-to-face and the learning steps are almost the same as offline learning.